Perencanaan Struktur Beton Bertulang Gedung Mal Pelayanan Publik Tahan Gempa Di Kabupaten Melawi - Khoir, Fatinnul; Sarimulyani, Sarimulyani; Syahrani, Deny; Ariyansyah, Rona (Teknik Sipil, Politeknik Negeri Ketapangg, 2024)
The Melawi Regency Public Service Mall Building is planned in West Kalimantan which is an area with low earthquake intensity. Every building structure in Indonesia needs to be planned to withstand earthquakes. The planned structural elements such as plates, beams, columns, and foundations must have sufficient strength to withstand earthquake loads in order to provide a sense of security for the occupants of the building. Structural planning uses reinforced concrete material according to SNI 2847-2019. The material quality used is concrete fc' 25 Mpa and 30 Mpa, reinforcement fy 420 Mpa and fy 280 Mpa. Structural loading refers to PPPURG 1987 and SNI 1727-2020. Earthquake load analysis uses the spectrum response method which refers to SNI 1726-2019. Modeling and structural analysis using the SAP2000 program. The results of determining the structural system obtained for the Public Service Mall building structure use the Ordinary Moment Bearing Frame System (SRPMB) as a seismic force resisting system. The calculation results obtained a 12 cm plate for the floor, 13 cm for the roof deck, 15 cm for the elevator pit, 20 cm for the stairs with D10 reinforcement. Dimension of main beam and bordes 30/50 cm, subsidiary beam and elevator 25/40 cm with D16 reinforcement. Column dimension 50/50 cm with 12D19 reinforcement. The foundation uses a pilecape measuring 150x150x50 cm with 4 piles with a diameter of 30/30 cm 14 m deep